2008
DOI: 10.1111/j.1365-2125.2008.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the absorption, metabolism and absolute bioavailability of maraviroc in healthy male subjects

Abstract: AIMSTwo studies were conducted to: (i) quantify the amount of drug-related radioactivity in blood, plasma, urine and faeces following a 14 C-labelled dose of maraviroc; and (ii) investigate the pharmacokinetics, safety and tolerability of intravenous (i.v.) maraviroc and determine the absolute bioavailability of oral maraviroc. Metabolite profiling was also conducted. Data from both of these studies were used to construct a mass-balance model for maraviroc. METHODSStudy 1 was an open-label study in three healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 7 publications
10
93
0
Order By: Relevance
“…1D). A secondary amine product resulting from N-dealkylation of maraviroc has been previously found in plasma and excreta (Abel et al, 2008a;Hyland et al, 2008). Therefore, to gain a more comprehensive view of maraviroc biotransformation, we also monitored the formation of this metabolite using our assay.…”
Section: Detection Of Monooxygenated Metabolites Of Maraviroc Using Umentioning
confidence: 99%
See 1 more Smart Citation
“…1D). A secondary amine product resulting from N-dealkylation of maraviroc has been previously found in plasma and excreta (Abel et al, 2008a;Hyland et al, 2008). Therefore, to gain a more comprehensive view of maraviroc biotransformation, we also monitored the formation of this metabolite using our assay.…”
Section: Detection Of Monooxygenated Metabolites Of Maraviroc Using Umentioning
confidence: 99%
“…In addition, there is increased interest in the development of maraviroc as an oral and/or topical microbicide for use in HIV prevention. Although maraviroc is known to be extensively metabolized to a number of products (Abel et al, 2008a), a comprehensive analysis of the biotransformation of maraviroc has yet to be reported. The cytochromes P450 (P450) are a superfamily of heme-containing monooxygenases that play a crucial role in drug clearance.…”
Section: Introductionmentioning
confidence: 99%
“…constant clearance and first-pass) [8]. It was further assumed that an infinitely high dose would be completely absorbed.…”
Section: Fqmentioning
confidence: 99%
“…The metabolite profiling of plasma, urine and fecal samples showed that maraviroc is extensively metabolized with the major pathways involving oxidation and N-dealkylation reactions (Figure 15) (Walker et al, 2005;Abel et al, 2008). The most abundant metabolite detected in human plasma was a secondary amine product of N-dealkylation (74, Figure 15).…”
Section: Co-receptor Inhibitors (Cris)mentioning
confidence: 99%